Weighted Gene Co-expression Network Analysis Identifies Specific Modules and Hub Genes Related to Subacute Ruminal Acidosis - Wang, Qiuju; Gao, Bingnan; Yue, Xueqing; Cui, Yizhe; Loor, Juan J.; Dai, Xiaoxia; Wei, Xu; Xu, Chuang (Frontiers in Veterinary Science, 2022)
Weighted gene co-expression network analysis (WGCNA) technology was used to explain the pathogenesis of subacute ruminal acidosis (SARA) and identify potential genes related to the disease in this study. Microarray data from GSE143765 dataset were downloaded from NCBI Gene Expression Omnibus (GEO) database, including 22 cows with subacute ruminal acidosis and 9 cows without subacute ruminal acidosis. Results of WGCNA analysis found modules of differentially expressed genes (DEGs) with high correlations, followed by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses to obtain further biological insight into the SARA related modules. The protein-protein interaction (PPI) network, the modules from the PPI network, and the gene annotation enrichment of modules were analyzed as well. We filtered 1944 genes that were considered significant DEGs for further WGCNA analysis. The Hub-Gene was identified as AURKB and GNAO1 by constructing a protein-protein network construction of the blue module, and functional annotation showed that GNAO1 is mainly involved in various transmembrane signaling systems as a regulator or transducer, while AURKB has transferase activity, transfer of phosphorus-containing motifs and protein tyrosine kinase activity, mainly as an association with microtubules during mitosis and meiosis through It is involved in the regulation of chromosome alignment and segregation. The results of this study may help to elucidate the pathophysiology of SARA development at the molecular level and explore the potential molecular mechanisms for new interventional strategies.